Bilayer electrolyte
By adopting a double-layer electrolyte structure in an all-solid-state battery pack, the lithium and PTFE fibres in the first layer react to form fibers containing carbon, fluorine and lithium, which solves the electrochemical and mechanical instability problems and achieves more Long cycle life and better lithium ion conduction.
Patent Information
- Application Number
- CN202311049417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The all-solid state battery pack has electrochemical instability between the anode layer and the solid electrolyte layer, resulting in an increase in cell resistance and mechanical instability associated with lithium dendrites during cycling.
A bilayer electrolyte structure is adopted, wherein the first layer comprises 10% to 40% of the first solid electrolyte particles, 1% to 15% of lithium and 1% to 65% of the fibrils containing carbon and fluorine, and the second layer comprises Two solid electrolyte particles. This structure forms a fibril containing carbon, fluorine and lithium by reaction of lithium and PTFE fibrils, providing mechanical and electrochemical stability.
It improves the electrochemical and mechanical stability of the battery, extends the cycle life of the solid-state battery pack, and enhances the conduction ability to lithium ions.
Smart Images

Figure CN119495803A_ABST
Abstract
Description
[0001] introduction
[0002] The present disclosure relates to solid-state batteries and methods of forming the same. More particularly, the present disclosure relates to electrolytes, such as sulfide electrolytes, having improved electrochemical and mechanical stability, and methods of making the same.
[0003] Electrochemical energy storage devices, such as lithium-ion batteries, can be used in a variety of products, including automotive products, such as start-stop systems (e.g., 12V start-stop systems), battery auxiliary systems ("μBAS"), hybrid electric vehicles ("HEV"), and electric vehicles ("EV"). A typical lithium-ion battery includes two electrodes and an electrolyte assembly and / or a separator. One of the two electrodes can serve as a positive electrode or cathode, and the other electrode can serve as a negative electrode or anode. The lithium-ion battery can also include various terminals and packaging materials. Rechargeable lithium-ion batteries operate by reversibly transferring lithium ions back and forth between the negative electrode and the positive electrode. For example, lithium ions can move from the positive electrode to the negative electrode during the battery charging process and move in the opposite direction when the battery is discharged. The separator and / or electrolyte can be disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions between the electrodes, and similar to the two electrodes, can be in solid form, liquid form, or a solid-liquid mixed form. In the case of a solid-state battery including a solid electrolyte layer disposed between solid electrodes, the solid electrolyte can physically separate the solid electrodes so that a separate separator is not required.
[0004] All-solid-state batteries (ASSBs), such as lithium-ion batteries (LIBs) including sulfide solid electrolytes, can provide desirable abuse tolerance, power capacity, and operating temperature range. However, electrochemical instabilities between the anode layer and the solid electrolyte layer can increase the cell resistance, and there can be poor mechanical stability associated with lithium dendrite growth during cycling. Therefore, it is desirable to provide a solid electrolyte layer with improved electrochemical and mechanical stability and methods of making the same. SUMMARY OF THE INVENTION
[0006] This application involves the following:
[0007] [1]. An electrolyte for an electrochemical cell, the electrolyte comprising:
[0008] a first layer having a thickness of about 1 μm to about 40 μm; and
[0009] a second layer having a thickness of about 5 μm to about 60 μm,
[0010] Wherein, based on the total weight of the first layer, the first layer comprises:
[0011] about 10 wt % to about 40 wt % of first solid electrolyte particles,
[0012] about 1 wt % to about 15 wt % lithium, and
[0013] about 1 wt % to about 65 wt % of fibrils comprising carbon and fluorine, and
[0014] The second layer comprises second solid electrolyte particles.
[0015] [2] The electrolyte as described in [1] above, wherein the first layer further comprises greater than 0 to about 60 wt % of a conductive material.
[0016] [3] The electrolyte as described in [1] above, wherein the first solid electrolyte particles are selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles and combinations thereof.
[0017] [4] The electrolyte as described in [1] above, wherein the second solid electrolyte particles are selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles and combinations thereof.
[0018] [5] The electrolyte described in [1] above, wherein the fibrils containing carbon and fluorine contain polytetrafluoroethylene.
[0019] [6] The electrolyte as described in [5] above, wherein the fibrils comprising polytetrafluoroethylene are present in an amount of about 1 wt % to about 50 wt % based on the total weight of the first layer.
[0020] [7] The electrolyte as described in [5] above, wherein the lithium is present in the form of lithium foil, stabilized lithium metal powder, lithium metal or a combination thereof.
[0021] [8] The electrolyte as described in [5] above, wherein the first layer further comprises a lithium anode material.
[0022] [9] The electrolyte described in [1] above, wherein the fibrils comprising carbon and fluorine further comprise lithium.
[0023]
[10] The electrolyte as described in [9] above, wherein the first layer further comprises a lithium anode material.
[0024]
[11] An electrochemical cell for circulating lithium ions, the electrochemical cell comprising:
[0025] An electrolyte comprising:
[0026] a first layer having a thickness of about 1 μm to about 40 μm; and
[0027] a second layer having a thickness of about 5 μm to about 60 μm,
[0028] Wherein, based on the total weight of the first layer, the first layer comprises:
[0029] about 10 wt % to about 40 wt % of first solid electrolyte particles;
[0030] about 1 wt % to about 15 wt % lithium;
[0031] From about 1% to about 65% by weight of fibrils comprising carbon and fluorine; and
[0032] greater than 0 to about 60 weight percent conductive material, and
[0033] The second layer comprises second solid electrolyte particles.
[0034]
[12] The electrochemical cell as described in
[11] above, wherein the first solid electrolyte particles are selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles and combinations thereof.
[0035]
[13] The electrochemical cell as described in
[11] above, wherein the second solid electrolyte particles are selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles and combinations thereof.
[0036]
[14] The electrochemical cell as described in
[11] above, wherein the electrochemical cell further comprises at least one first electrode, wherein the at least one first electrode comprises:
[0037] a first solid electroactive particle, and
[0038] Third solid electrolyte particles.
[0039]
[15] The electrochemical cell as described in
[14] above, wherein the electrochemical cell further comprises at least one second electrode, wherein the at least one second electrode comprises:
[0040] a second solid electroactive particle, wherein the second solid electroactive particle is different from the first solid electroactive particle, and
[0041] Fourth solid electrolyte particles.
[0042]
[16] . The electrochemical cell as described in
[13] above, wherein the fibrils comprising carbon and fluorine comprise polytetrafluoroethylene.
[0043]
[17] . The electrochemical cell as described in
[13] above, wherein the fibrils comprising carbon and fluorine further comprise lithium.
[0044]
[18] . An electrolyte for an electrochemical cell, the electrolyte comprising:
[0045] a first layer having a thickness of about 1 μm to about 40 μm; and
[0046] a second layer having a thickness of about 5 μm to about 60 μm,
[0047] Wherein, based on the total weight of the first layer, the first layer comprises:
[0048] about 10 wt % to about 40 wt % of first solid electrolyte particles, wherein the first solid electrolyte particles comprise solid sulfide electrolyte particles;
[0049] about 1 wt % to about 15 wt % lithium;
[0050] From about 1% to about 65% by weight of fibrils comprising carbon and fluorine; and
[0051] greater than 0 to about 60 weight percent conductive material, and
[0052] The second layer comprises second solid electrolyte particles.
[0053]
[19] . The electrolyte as described in
[17] above, wherein the first solid electrolyte particles further comprise solid halide electrolyte particles, solid hydride electrolyte particles, or a combination of solid halide electrolyte particles and solid hydride electrolyte particles.
[0054]
[20] . The electrolyte as described in
[17] above, wherein the fibrils comprising carbon and fluorine are prepared from a starting polytetrafluoroethylene material having an average particle size of greater than or equal to about 2 μm to less than or equal to about 2,000 μm.
[0055] In one exemplary embodiment, the present disclosure provides an electrolyte for an electrochemical cell. The electrolyte may include first solid electrolyte particles and fibrils comprising carbon and fluorine, the fibrils providing a structural framework for the first solid electrolyte particles.
[0056] In addition to one or more features described herein, the electrolyte includes a first layer having a thickness of about 1 micrometer (μm) to about 40 μm and a second layer having a thickness of about 5 μm to about 60 μm. Based on the total weight of the first layer, the first layer may include: about 10 weight percent (wt%) to about 40 wt% of first solid electrolyte particles, about 1 wt% to about 15 wt% of lithium, and about 1 wt% to about 65 wt% of fibrils containing carbon and fluorine. The second layer may include second solid electrolyte particles.
[0057] In another exemplary embodiment, the first layer may further include greater than 0 to about 60 weight percent of a conductive material.
[0058] In yet another exemplary embodiment, the first solid electrolyte particles may be selected from the group consisting of solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles, and combinations thereof.
[0059] In yet another exemplary embodiment, the second solid electrolyte particles may be selected from the group consisting of solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles, and combinations thereof.
[0060] In yet another exemplary embodiment, the carbon and fluorine containing fibrils may include polytetrafluoroethylene (PTFE).
[0061] In yet another exemplary embodiment, the fibrils comprising PTFE may be present in an amount of about 1 wt % to about 50 wt %, based on the total weight of the first layer.
[0062] In yet another exemplary embodiment, the lithium may be present in the form of lithium foil, stabilized lithium metal powder, lithium metal, or a combination thereof.
[0063] In yet another exemplary embodiment, the first layer may further include a lithium anode material.
[0064] In yet another exemplary embodiment, the fibrils comprising carbon and fluorine may further comprise lithium.
[0065] In yet another exemplary embodiment, the first layer may further include a lithium anode material.
[0066] In an exemplary embodiment, the present disclosure provides an electrochemical cell for circulating lithium ions. The electrochemical cell may include an electrolyte comprising a first layer having a thickness of about 1 μm to about 401 μm, and a second layer having a thickness of about 5 μm to about 60 μm. Based on the total weight of the first layer, the first layer may include: about 10 wt % to about 40 wt % of first solid electrolyte particles, about 1 wt % to about 15 wt % of lithium, about 1 wt % to about 65 wt % of fibrils comprising carbon and fluorine, and greater than 0 to about 60 wt % of conductive material. The second layer may include second solid electrolyte particles.
[0067] In addition to one or more features described herein, the first solid electrolyte particles may be selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles, and combinations thereof.
[0068] In another exemplary embodiment, the second solid electrolyte particles may be selected from: solid sulfide electrolyte particles, solid halide electrolyte particles, solid hydride electrolyte particles, and combinations thereof.
[0069] In yet another exemplary embodiment, the electrochemical cell may further include at least one first electrode. The at least one first electrode may include first solid electroactive particles and third solid electrolyte particles.
[0070] In yet another exemplary embodiment, the electrochemical cell may further include at least one second electrode. The at least one second electrode may include second solid-state electroactive particles, third solid-state electrolyte particles, and fourth solid-state electrolyte particles. The second solid-state electroactive particles may be different from the first solid-state electroactive particles.
[0071] In yet another exemplary embodiment, the carbon and fluorine containing fibrils may include PTFE.
[0072] In yet another exemplary embodiment, the fibrils comprising carbon and fluorine may further comprise lithium.
[0073] In an exemplary embodiment, the present disclosure provides an electrolyte for an electrochemical cell. The electrolyte may include a first layer having a thickness of about 1 μm to about 40 μm and a second layer having a thickness of about 5 μm to about 60 μm. Based on the total weight of the first layer, the first layer may include: about 10 wt % to about 40 wt % of first solid electrolyte particles, wherein the first solid electrolyte particles may include solid sulfide electrolyte particles; about 1 wt % to about 15 wt % of lithium; about 1 wt % to about 65 wt % of fibrils comprising carbon and fluorine; and greater than 0 to about 60 wt % of conductive material. The second layer may include second solid electrolyte particles.
[0074] In addition to one or more features described herein, the first solid electrolyte particles may further include solid halide electrolyte particles, solid hydride electrolyte particles, or a combination of solid halide electrolyte particles and solid hydride electrolyte particles.
[0075] In another exemplary embodiment, the carbon and fluorine containing fibrils can be prepared from a starting PTFE material having an average particle size of greater than or equal to about 2 μm to less than or equal to about 2,000 μm.
[0076] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings.
[0077] BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Additional features, advantages and details are set forth, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0079] Figure 1 is a diagram showing formation of an electrolyte layer according to one aspect of the present disclosure;
[0080] Figure 2 is a diagram showing formation of an electrolyte layer according to one aspect of the present disclosure;
[0081] Figure 3 is a diagram showing formation of an electrolyte layer according to one aspect of the present disclosure;
[0082] Figure 4 is a diagram showing formation of an electrolyte layer according to one aspect of the present disclosure;
[0083] Figure 5 is an illustration of a portion of a battery pack according to one aspect of the present disclosure;
[0084] Figure 6 is a scanning electron microscope (SEM) image of a comparative example;
[0085] Figure 7 is a SEM image of an embodiment;
[0086] Figure 8 is a graphical representation of an x-ray photoelectron spectroscopy (XPS) analysis of a first layer of an example;
[0087] Fig. 9 is a diagram showing the electrochemical performance of a comparative example;
[0088] Fig.10 is a graphical representation showing the electrochemical performance of a comparative example; and
[0089] Fig.11 is a graph showing the electrochemical performance of comparative examples and examples. DETAILED DESCRIPTION OF THE INVENTION
[0091] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.
[0092] According to an exemplary embodiment, an electrolyte for a solid-state battery (SSB), and methods of forming and using the same are disclosed. The solid-state battery may include at least one solid component, such as at least one solid electrode, but in certain variations may also include a semi-solid or gel, liquid or gas component. In various cases, the solid-state battery may have a bipolar stack design comprising a plurality of bipolar electrodes, wherein a first mixture of solid-state electroactive material particles (and optional solid-state electrolyte particles) is disposed on a first side of a current collector, and a second mixture of solid-state electroactive material particles (and optional solid-state electrolyte particles) is disposed on a second side of the current collector parallel to the first side. The first mixture may include cathode material particles as solid-state electroactive material particles. The second mixture may include anode material particles as solid-state electroactive material particles. In each case, the solid-state electrolyte particles may be the same or different.
[0093] In other variations, the solid-state battery pack may have a monopolar stack design comprising multiple monopolar electrodes, wherein a first mixture of solid-state electroactive material particles (and optional solid-state electrolyte particles) is disposed on a first side and a second side of a first current collector, wherein the first side and the second side of the first current collector are substantially parallel, and a second mixture of solid-state electroactive material particles (and optional solid-state electrolyte particles) is disposed on a first side and a second side of a second current collector, wherein the first side and the second side of the second current collector are substantially parallel. The first mixture may include cathode material particles as solid-state electroactive material particles. The second mixture may include anode material particles as solid-state electroactive material particles. The solid-state electrolyte particles may be the same or different in each case. In certain variations, the solid-state battery pack may include a mixture of combinations of bipolar and monopolar stack designs.
[0094] Such solid-state batteries can be incorporated into energy storage devices, such as rechargeable lithium-ion batteries, which can be used in automotive transportation applications (e.g., motorcycles, boats, tractors, buses, mobile homes, campers, and tanks). However, the present technology can also be used in other electrochemical devices, including, as non-limiting examples, aerospace parts, consumer products, devices, buildings (e.g., houses, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery. In various aspects, the present disclosure provides a rechargeable lithium-ion battery that exhibits high temperature tolerance as well as improved safety and excellent power capacity and life performance.
[0095] A solid-state battery (SSB) may include an anode comprising graphite and Li6PS5Cl (LPSCl) in a weight ratio of 6:4 graphite:LPSCl, a cathode comprising a composition of 50% nickel, 30% manganese and 20% cobalt (NCM523) and LPSCl in a weight ratio of 7:3 NCM523:LPSCl, and an electrolyte comprising LPSCl therebetween. Interfacial side reactions may occur between the solid electrolyte (LPSCl) and the anode, which may result in poor electrochemical stability of the sulfide (e.g., 1.7 volts (V)). In addition, dendrites may grow along the solid electrolyte (LPSCl) (e.g., adjacent to the anode). There may be low kinetic energy between the anode material and the sulfide electrolyte (LPSCl). The interface that may be formed by the side reactions between the solid electrolyte and the anode may be ineffective in suppressing dendrite growth, and internal short circuits may occur after cycling.
[0096] Therefore, there may be electrochemical instabilities between the anode and the solid electrolyte, and mechanical instabilities with lithium dendrites growing across the interface upon cycling. If lithium dendrites grow within the solid electrolyte, the lithium may become inactive, and internal short circuits may occur if lithium dendrites grow across the anode and reach the cathode. Electrochemically and mechanically stable electrolyte layers are required for extended solid-state battery cycling.
[0097] The disclosed double-layer electrolyte includes a first layer (also referred to herein as a "protective layer") and a second layer (also referred to herein as a "solid electrolyte" layer). The first layer can provide mechanical and / or electrochemical stability. The strong fibril framework in the first layer can provide mechanical stability.
[0098] In certain variations, the starting polymer or polymer binder (e.g., generating or forming PTFE fibrils) may have an average particle size of greater than or equal to about 2 μm to less than or equal to about 2,000 μm, and in certain aspects greater than or equal to about 300 μm to less than or equal to about 800 μm, or greater than or equal to about 400 μm to less than or equal to about 700 μm. It is worth noting that polyvinylidene fluoride (PVDF), polypropylene (PP), and polyethylene (PE) materials have not been found to produce usable fibrils.
[0099] Hereinafter, although reference may be made to PTFE fibrils, it should be understood that any suitable polymer may be used to form the fibers. For example, other suitable polymers include fluorinated ethylene propylene (FEP), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETF) or combinations thereof. Additional polymers with desirable film-forming properties and high film elongation under calendering include, for example, polyvinylidene fluoride-hexafluoropropylene (PVF-co-hexafluoropropylene), polyvinylidene fluoride-trichloroethylene (PVF-co-trichloroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymers, and polyimides.
[0100] The PTFE fibrils may have an average length of greater than or equal to about 2 μm to less than or equal to about 100 μm. The PTFE fibrils may have an average length of greater than or equal to about 2 μm to less than or equal to about 100 μm. The PTFE fibrils may have a softening point of greater than or equal to about 270° C. to less than or equal to about 380° C. The PTFE fibrils may have a softening point of greater than or equal to 270° C. to less than or equal to 380° C. The molecular weight of the PTFE fibrils may be greater than or equal to about 10 5 Grams / mole (g / mol) to less than or equal to about 10 9 The molecular weight of the PTFE fibrils can be greater than or equal to 10 5 g / mol to less than or equal to 10 9 g / mol.
[0101] Reference Figure 1 , the first layer 100 may include PTFE fibrils 10, lithium 20, first solid electrolyte particles 30, and conductive material 40. The PTFE fibrils 10 within the first layer 100 may spontaneously react with the lithium 20 also present in the first layer 100 according to the following reaction:
[0102] -(CF2-CF2) n -+4nLi→2nC+4nLiF
[0103] The fibrils 50 comprising carbon, fluorine and lithium are formed in situ. The fibrils 50 comprising carbon, fluorine and lithium can help reduce or prevent electrochemical reduction of the second layer and enable uniform Li+ with reduced or no lithium dendrite growth. +The residual PTFE can inhibit lithium dendrite growth through the reaction of PTFE fibrils 10 with lithium 20. Since dendrite growth has been reduced or eliminated, a relatively thin second layer can be included in the solid-state battery.
[0104] The fibrils 50 comprising carbon, fluorine and lithium can provide a strong first layer and help provide desirable electrochemical stability and high lithium ion conductivity; the solid electrolyte particles 30 can promote smooth lithium ion pathways in the layer; and the optional conductive material 40 can help provide uniform Li in the interface. + distribution, for example, due to the excellent Li + affinity, which may enable uniform Li + Flux and rapid Li across the interface of the fibrils 50 comprising carbon, fluorine and lithium + migrate.
[0105] Different starting amounts of lithium and PTFE can lead to different reaction products. The stoichiometric ratio of lithium to -[CF2-CF2]- is 4:1. Figure 2 As shown in FIG. 1 , if lithium is in excess, the first layer including the fibrils 50 including carbon, fluorine, and lithium may include lithium 20 separated from the fibrils 50. Figure 3 As shown in , if PTFE is in excess, a portion of the PTFE may be converted to fibrils 50 comprising carbon, fluorine, and lithium, and residual PTFE fibrils may remain (eg, to help serve as a framework in the first layer).
[0106] Reference Figure 4 , the first layer 100 may include a mixture 25 of lithium and lithium anode material, which may react according to the following reaction:
[0107] -(CF2-CF2) n -+4nLi-M→2nC+4nLiF+4nM - A first layer including fibrils 50 comprising carbon, fluorine and lithium and a lithium anode material 60 is formed.
[0108] To form a first layer including fibrils 50 comprising carbon, fluorine and lithium, first mix the solid electrolyte, PTFE powder, lithium powder and optional conductive material (e.g., graphite). After continuous mixing and shearing, the PTFE can be fully fibrillated (e.g., fully fibrillated), which can effectively adhere to the lithium, solid electrolyte and conductive material, holding them together like a spider web. Secondly, spread the mixture (e.g., on the anode) to form a protective layer thereon. Third, in situ form the fibrils 50 comprising carbon, fluorine and lithium and manufacture the solid-state battery pack.
[0109] Without wishing to be bound by any theory, it is believed that the fibrils 50 comprising carbon, fluorine and lithium may include small inorganic particles (e.g., comprising lithium) on the surface of the polymer chains of the PTFE fibrils 10. The fibrils 50 comprising carbon, fluorine and lithium may have an average length of greater than or equal to about 2 μm to less than or equal to about 100 μm.
[0110] The fibrillated PTFE when first formed can be characterized as fibrils comprising carbon and fluorine or fibrils comprising PTFE. The fibrils comprising carbon, fluorine and lithium 50 formed in situ from fibrils comprising PTFE can also be characterized as fibrils comprising carbon and fluorine, wherein such fibrils further include lithium.
[0111] The lithium present in the first layer before the PTFE fibrils 10 react with the lithium 20 may be in the form of lithium foil, stabilized lithium metal powder, lithium metal, or a combination thereof. The lithium anode material that may be present in the first layer before the PTFE fibrils 10 react with the lithium 20 may include, for example, a carbonaceous material (e.g., graphite, hard carbon, soft carbon, or a combination thereof), a metal oxide or sulfide (e.g., TiO2, FeS, or a combination thereof), Li4Ti5O 12 and other lithium receiving anode materials; Li alloy type materials (such as silicon, silicon oxide (SiO) or silicon compounds, transition metals (such as Sn, In) or combinations thereof); or combinations thereof.
[0112] A solid-state electrochemical cell (also referred to as a "solid-state battery" and / or "battery") that circulates lithium ions may include a negative electrode (i.e., an anode), a positive electrode (i.e., a cathode), and an electrolyte that occupies a space defined between two or more electrodes. The electrolyte is a solid or semi-solid separator that physically separates the negative electrode from the positive electrode. The electrolyte may include a first layer and a second layer. The first layer may include first solid electrolyte particles and fibrils comprising carbon, fluorine, and lithium. The second layer may include second solid electrolyte particles. Third solid electrolyte particles may be mixed with solid negative electroactive particles in the negative electrode, and fourth solid electrolyte particles may be mixed with solid positive electroactive particles in the positive electrode to form a continuous electrolyte network, which may be a continuous lithium ion conducting network.
[0113] The first current collector may be located at or near the negative electrode. The first current collector may be a metal foil, a metal grid or a mesh, or a porous metal comprising copper or any other suitable conductive material known to those skilled in the art. The second current collector may be located at or near the positive electrode. The second current collector may be a metal foil, a metal grid or a mesh, or a porous metal comprising aluminum or any other suitable conductive material known to those skilled in the art. The first current collector and the second current collector may be the same or different. The first current collector and the second electrode current collector respectively collect free electrons from an external circuit and move the free electrons to the external circuit. For example, an interruptible external circuit and a load device may connect the negative electrode (via the first current collector) and the positive electrode (via the second current collector).
[0114] The skilled person will recognize that in some variations, the first current collector may be a first bipolar current collector and / or the second current collector may be a second bipolar current collector. For example, the first bipolar current collector and / or the second bipolar current collector may be a coated foil, for example, wherein one side of the current collector (e.g., the first side or the second side) includes a metal (e.g., a first metal), and the other side of the current collector (e.g., the other side of the first side or the second side) includes another metal (e.g., a second metal). The coated foil may include (e.g., only include) aluminum-copper (Al-Cu), nickel-copper (Ni-Cu), stainless steel-copper (SS-Cu), aluminum-nickel (Al-Ni), aluminum-stainless steel (Al-SS), and nickel-stainless steel (Ni-SS). In some variations, the first bipolar current collector and / or the second bipolar current collector may be pre-coated, such as a graphene or carbon-coated aluminum current collector.
[0115] The battery can generate current during discharge by a reversible electrochemical reaction that occurs when an external circuit is closed (to connect the negative electrode and the positive electrode) and when the negative electrode has a lower potential than the positive electrode. The chemical potential difference between the negative electrode and the positive electrode drives the electrons generated at the negative electrode through a reaction such as oxidation of intercalated lithium toward the positive electrode through the external circuit. Lithium ions also generated at the negative electrode are simultaneously transferred toward the positive electrode through the electrolyte. Electrons flow through the external circuit and lithium ions migrate across the electrolyte to the positive electrode, where they can plate, react or embed. The current through the external circuit can be harnessed and directed through the load device (in the direction of the arrow) until the lithium in the negative electrode is exhausted and the capacity of the battery is reduced.
[0116] An external power source (e.g., a charging device) can be connected to the battery pack to reverse the electrochemical reactions that occur during the discharge of the battery pack, thereby charging or re-energizing the battery pack at any time. The external power source that can be used to charge the battery pack can be different depending on the size, construction, and specific end use of the battery pack. Some notable and exemplary external power sources include, but are not limited to, AC (AC)-DC (DC) converters and motor vehicle alternators that are connected to the AC power grid via a wall outlet. Connecting an external power source to the battery pack promotes reactions at the positive electrode, such as non-spontaneous oxidation of embedded lithium, thereby generating electrons and lithium ions. Electrons (which flow back to the negative electrode through an external circuit) and lithium ions (which move back to the negative electrode across the electrolyte) recombine at the negative electrode and replenish it with lithium so that it is consumed during the next battery pack discharge cycle. Thus, a complete discharge event followed by a complete charge event is considered to be a cycle in which lithium ions circulate between the positive and negative electrodes.
[0117] Although the described examples include a single positive electrode and a single negative electrode, the skilled person will recognize that the present teachings are applicable to various other configurations, including those having one or more cathodes and one or more anodes, and various current collectors and current collector films having an electroactive particle layer disposed on or adjacent to one or more surfaces thereof or embedded in one or more surfaces thereof. Similarly, it should be appreciated that the battery pack may include a variety of other components, which, although not depicted herein, are still known to those skilled in the art. For example, the battery pack may include a housing, a gasket, an end cap, and any other conventional components or materials that may be located within the battery pack (including between or around the negative electrode, positive electrode, and / or electrolyte).
[0118] In many configurations, each of the first current collector, the negative electrode, the electrolyte, the positive electrode, and the second current collector is prepared as a relatively thin layer (e.g., a few microns to a millimeter or less in thickness) and assembled in a layer connected in a series arrangement to provide suitable power, battery voltage, and power packaging, such as obtaining a series-connected unit cell core ("SECC"). In various other cases, the battery may further include electrodes connected in parallel to provide suitable power, battery voltage, and power, such as obtaining a parallel-connected unit cell core ("PECC").
[0119] The size and shape of the battery pack can vary according to the specific application for which it is designed. Vehicles and handheld consumer electronic devices powered by battery packs are two examples in which the battery pack is most likely to be designed to different sizes, capacities, voltages, energy and power output specifications. The battery pack can also be connected in series or in parallel with other similar lithium-ion batteries or battery packs to produce greater voltage output, energy and power (if the load device requires it). The battery pack can generate a current toward the load device, which can be operably connected to an external circuit. The load device can be powered in whole or in part by the current through the external circuit when the battery pack is discharged. Although the load device can be any number of known electric devices, as non-limiting examples, some specific examples of power-consuming load devices include motors, laptop computers, tablet computers, cellular phones and cordless power tools or appliances for hybrid electric vehicles or all-electric vehicles. The load device can also be a power generation device for charging the battery pack in order to store electrical energy.
[0120] The electrolyte provides electrical separation (e.g., prevents physical contact) between the negative electrode and the positive electrode. The electrolyte also provides a path of least resistance for the internal passage of lithium ions. The electrolyte can be a membrane. That is, the electrolyte can be self-supporting, have structural integrity, and can be processed as an independent layer (e.g., removed from a substrate), rather than a coating formed on another component.
[0121] Figure 5 A portion of a battery pack 900 is shown, which includes an electrolyte 1000, a negative electrode (eg, an anode) 2000, and a positive electrode (eg, a cathode) 3000. Figure 5 In various aspects, the electrolyte 1000 includes a first layer 100, which includes first solid electrolyte particles 30, a conductive material 40, and fibrils 50 containing carbon, fluorine, and lithium; and a second layer 200, which includes second solid electrolyte particles 35. The fibrils 50 containing carbon, fluorine, and lithium can provide a structural framework for the first solid electrolyte particles 30 and the optional conductive material. For example, the first layer 100 can be in the form of a composite material, which includes first solid electrolyte particles 30, a conductive material 40, and fibrils 50 containing carbon, fluorine, and lithium. The first layer 100 can have a thickness greater than or equal to about 1 μm to less than or equal to about 40 μm. The second layer 200 can have a thickness greater than or equal to 5 μm to less than or equal to 60 μm.
[0122] The first layer is adjacent to the negative electrode (e.g., anode) 2000 and the second layer 200 is adjacent to the positive electrode (e.g., cathode) 3000. As shown, the negative electrode (e.g., anode) 2000 includes third solid electrolyte particles 70 and solid negative electroactive particles 80, and the positive electrode (e.g., cathode) 3000 includes fourth solid electrolyte particles 75 and solid positive electroactive particles 90.
[0123] Before the PTFE fibrils 10 react with the lithium 20, the first layer 100 may include greater than or equal to about 1 wt % to less than or equal to about 50 wt % of the fibrils 10 (e.g., PTFE fibrils 10), greater than or equal to about 1 wt % to less than or equal to about 15 wt % of the lithium 20, greater than or equal to about 10 wt % to less than or equal to about 40 wt % of the first solid electrolyte particles 30 (e.g., Li6PS5Cl or Li 10 GeP2S 12 (LGPS)), and optionally greater than 0 wt% to less than or equal to about 60 wt% of a conductive material 40 (e.g., graphite). For example, the first layer may include 1 wt% of PTFE fibrils, 1.5 wt% of Li, 39.5 wt% of LPSCl, and 58 wt% of graphite. During the reaction of the PTFE fibrils 10 with lithium 20, lithium may be incorporated into the fibrils, and after the reaction of the PTFE fibrils 10 with lithium 20, the first layer 100 may include greater than or equal to about 1 wt% to less than or equal to about 65 wt% of the fibrils 50 containing carbon, fluorine, and lithium, greater than or equal to about 10 wt% to less than or equal to about 40 wt% of the first solid electrolyte particles 30 (e.g., Li6PS5Cl or Li 10 GeP2S 12 (LGPS)), and optionally greater than 0 wt % to less than or equal to about 60 wt % of a conductive material 40 (eg, graphite).
[0124] In certain variations, the first solid electrolyte particles 30 and / or the second solid electrolyte particles 35 may each independently have an average particle size of greater than or equal to about 0.02 μm to less than or equal to about 20 μm, optionally greater than or equal to about 0.1 μm to less than or equal to about 10 μm, and in certain aspects, optionally greater than or equal to about 0.1 μm to less than or equal to about 1 μm. The first solid electrolyte particles 30 and / or the second solid electrolyte particles 35 may each independently have an average particle size of greater than or equal to 0.02 μm to less than or equal to 20 μm, optionally greater than or equal to 0.1 μm to less than or equal to 10 μm, and in certain aspects, optionally greater than or equal to 0.1 μm to less than or equal to 1 μm. For example, the first solid electrolyte particles 30 and / or the second solid electrolyte particles 35 may each independently include one or more sulfide-based particles, halide-based particles, hydride-based particles, or other solid electrolyte particles, such as having low grain boundary resistance. The second solid electrolyte particles 35 may be the same as or different from the first solid electrolyte particles 30 .
[0125] In various aspects, the sulfide-based particles may include pseudo-binary sulfide systems, pseudo-ternary sulfide systems, and / or pseudo-quaternary sulfide systems. Exemplary pseudo-binary sulfide systems include Li2S-P2S5 systems (e.g., Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), Li2S-SnS2 system (such as Li4SnS4), Li2S-SiS2 system, Li2S-GeS2 system, Li2S-B2S3 system, Li2S-Ga2S3 system, Li2S-P2S3 system and Li2S-Al2S3 system. Exemplary pseudo-ternary sulfide systems include Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system (such as Li 3.25 Ge 0.25 P 0.75 S4 and Li 10 GeP2S 12 (LGPS)), Li2S-P2S5-LiX system (wherein X is one of F, Cl, Br and I) (such as Li6PS5Br, Li6PS5Cl, L7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (such as Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 system (where X is one of F, Cl, Br and I), 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 Exemplary pseudo-quaternary sulfide systems include the Li2O-Li2S-P2S5-P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 and Li 10.35 『Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0126] In various aspects, the halide-based particles may include (e.g., only include) Li3YCl6, Li3InCl6, Li3YBr6, LiI, Li2CdC 14, Li2MgCl4, LiCdI4, Li2ZnI4, Li3Ocl and combinations thereof; and the hydride-based particles may include (e.g., only include) LiBH4, LiBH4-LiX (wherein x=Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6 and combinations thereof.
[0127] The negative electrode can be formed of a lithium matrix material capable of acting as a negative terminal of a lithium ion battery. For example, in some variations, the negative electrode can be defined by a plurality of solid negatively electrically active particles. In some cases, the negative electrode is a composite material comprising a mixture of solid negatively electrically active particles and third solid electrolyte particles. In each variation, the negative electrode can be in the form of a layer having a thickness of greater than or equal to about 10 μm to less than or equal to about 5,000 μm, for example, greater than or equal to about 10 μm to less than or equal to about 500 μm and in some aspects optionally greater than or equal to about 10 μm to less than or equal to about 100 μm, for example, about 20 μm.
[0128] The negative electrode may include greater than or equal to about 30 wt % to less than or equal to about 98 wt %, and in some aspects optionally greater than or equal to about 50 wt % to less than or equal to about 95 wt % of solid negative electroactive particles, and greater than or equal to 0 wt % to less than or equal to about 50 wt %, and in some aspects optionally greater than or equal to about 5 wt % to less than or equal to about 20 wt % of the third solid electrolyte particles. The negative electrode may include greater than or equal to 30 wt % to less than or equal to 98 wt %, and in some aspects optionally greater than or equal to 50 wt % to less than or equal to 95 wt % of solid negative electroactive particles, and greater than or equal to 0 wt % to less than or equal to 50 wt %, and in some aspects optionally greater than or equal to 5 wt % to less than or equal to 20 wt % of the third solid electrolyte particles.
[0129] The solid negative electroactive particles can be lithium-based, such as lithium alloys or lithium metal. In other variations, the solid negative electroactive particles can be silicon-based, including, for example, silicon alloys and / or silicon-graphite mixtures. In still other variations, the negative electrode can be a carbonaceous anode, and the solid negative electroactive particles can include one or more negative electroactive materials, such as graphite, graphene, hard carbon, soft carbon, and carbon nanotubes (CNTs). In still further variations, the negative electrode can include one or more negative electroactive materials, such as lithium titanium oxide (Li4Ti5O 12 ); one or more metal oxides, such as TiO2 and / or V2O5; and / or metal sulfides, such as FeS. The solid negatively electroactive particles can be selected from the group including (e.g., only including) lithium, graphite, graphene, hard carbon, soft carbon, carbon nanotubes, silicon, silicon-containing alloys, tin-containing alloys and / or other lithium receiving materials.
[0130] The third solid electrolyte particles may be the same as or different from the first solid electrolyte particles and / or the second solid electrolyte particles. For example, the third solid electrolyte particles may include one or more sulfide-based particles, halide-based particles, hydride-based particles, or other solid electrolyte particles, for example, having low grain boundary resistance.
[0131] In some variations, the negative electrode may further include one or more conductive additives and / or binder materials. For example, the solid negative electroactive particles (and / or third solid electrolyte particles) may be optionally mixed with one or more conductive materials that provide an electronic conduction path and / or at least one polymer binder material that improves the structural integrity of the negative electrode.
[0132] For example, the solid negatively charged particles (and / or the third solid electrolyte particles) may be optionally mixed with a binder, such as sodium carboxymethylcellulose (CMC), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), PVDF, PTFE, ethylene propylene diene monomer (EPDM) rubber, nitrile rubber (NBR), styrene-butadiene rubber (SBR), polyethylene glycol (PEO) and / or lithium polyacrylate (LiPAA) binder. The conductive material may include, for example, a carbon-based material or a conductive polymer. The carbon-based material may include, for example, graphite particles, acetylene black (such as KETCHEN TM Black or DENKA TM Black), carbon nanofibers and nanotubes, graphene (such as graphene oxide), carbon black (such as Super P), etc. Examples of conductive polymers may include polyaniline, polythiophene, polyacetylene, polypyrrole, etc. In some aspects, a mixture of conductive additives and / or binder materials can be used.
[0133] In various aspects, the negative electrode may include greater than or equal to 0 wt % to less than or equal to about 30 wt %, and in certain aspects, optionally greater than or equal to about 2 wt % to less than or equal to about 10 wt % of one or more conductive additives; and greater than or equal to 0 wt % to less than or equal to about 20 wt %, and in certain aspects, optionally greater than or equal to about 1 wt % to less than or equal to about 10 wt % of one or more binders. The negative electrode may include greater than or equal to 0 wt % to less than or equal to 30 wt %, and in certain aspects, optionally greater than or equal to 2 wt % to less than or equal to 10 wt % of one or more conductive additives; and greater than or equal to 0 wt % to less than or equal to 20 wt %, and in certain aspects, optionally greater than or equal to 1 wt % to less than or equal to 10 wt % of one or more binders.
[0134] The positive electrode can be formed from a lithium-based or electroactive material that can undergo lithium intercalation and deintercalation while serving as the positive terminal of the battery pack. For example, in some variations, the positive electrode can be defined by a plurality of solid-state positive electroactive particles. In some cases, the positive electrode is a composite material comprising a mixture of solid-state positive electroactive particles and fourth solid-state electrolyte particles. In each variation, the positive electrode can be in the form of a layer having a thickness greater than or equal to about 10 μm to less than or equal to about 5,000 μm, such as greater than or equal to about 10 μm to less than or equal to about 500 μm, and in some aspects optionally greater than or equal to about 10 μm to less than or equal to about 100 μm, such as about 40 μm.
[0135] The positive electrode can comprise greater than or equal to about 30 wt% to less than or equal to about 98 wt%, and in some aspects optionally greater than or equal to about 50 wt% to less than or equal to about 95 wt% of solid-state positive electroactive particles, and greater than or equal to 0 wt% to less than or equal to about 50 wt%, and in some aspects optionally greater than or equal to about 5 wt% to less than or equal to about 20 wt% of fourth solid-state electrolyte particles. The positive electrode can comprise greater than or equal to 30 wt% to less than or equal to 98 wt%, and in some aspects optionally greater than or equal to 50 wt% to less than or equal to 95 wt% of solid-state positive electroactive particles, and greater than or equal to 0 wt% to less than or equal to 50 wt%, and in some aspects optionally greater than or equal to 5 wt% to less than or equal to 20 wt% of fourth solid-state electrolyte particles.
[0136] In some variations, the positive electrode can be one of a layered oxide cathode, a spinel cathode, and a polyanion cathode. For example, in the case of a layered oxide cathode (such as a rock salt layered oxide), the solid-state positive electroactive particles can comprise one or more electroactive materials selected, for a solid-state lithium-ion battery pack, from LiCoO2, LiNi x Mn y Co 1-x-y O2 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), LiNi x Mn y Al 1-x-y O2 (where 0 < x ≤ 1 and 0 < y ≤ 1), LiNi x Mn 1-x O2 (where 0 ≤ x ≤ 1) and Li 1+x MO2 (where 0 ≤ x ≤ 1). The spinel cathode can comprise one or more electroactive materials such as LiMn2O4 and LiNi 0.5 Mn 1.5O4. The polyanion cathode may include, for example, a phosphate such as LiFePO4, LiVPO4, LiV2(PO4)3, Li2FePO4F, Li3Fe3(PO4)4 or Li3V2(PO4)F3 for a lithium ion battery, and / or a silicate such as LiFeSiO4 for a lithium ion battery. The solid positively electroactive particles may include one or more positively electroactive materials selected from LiCoO2, LiNi x Mn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), Li 1+x MO2 (where 0≤x≤1), LiMn2O4, LiNi x Mn 1.5 O4, LiFePO4, LiVPO4, LiV2(PO4)3, Li2FePO4F, Li3Fe3(PO4)4, Li3V2(PO4)F3, LiFeSiO4 and combinations thereof. In certain aspects, the solid positive electroactive particles can be coated (e.g., with LiNbO3 and / or Al2O3) and / or the positive electroactive material can be doped (e.g., with aluminum and / or magnesium).
[0137] The fourth solid electrolyte particles may be the same as or different from the first solid electrolyte particles, the second solid electrolyte particles and / or the third solid electrolyte particles. For example, the fourth solid electrolyte particles may include one or more sulfide-based particles, halide-based particles, hydride-based particles or other solid electrolyte particles, for example, having low grain boundary resistance.
[0138] In some variations, the positive electrode may further include one or more conductive additives and / or binder materials. For example, the solid positive electroactive particles (and / or fourth solid electrolyte particles) may be optionally mixed with one or more conductive materials that provide an electronic conduction path and / or at least one polymer binder material that improves the structural integrity of the positive electrode.
[0139] For example, the solid positively electroactive particles (and / or the fourth solid electrolyte particles) may be optionally mixed with a binder, such as sodium CMC, SEBS, SBS, PVDF, PTFE, EPDM rubber, NBR, SBR, PEO and / or LiPAA binders. The conductive material may include, for example, a carbon-based material or a conductive polymer. The carbon-based material may include, for example, graphite particles, acetylene black (such as KETCHEN TM Black or DENKA TMBlack), carbon nanofibers and nanotubes, graphene (such as graphene oxide), carbon black (such as Super P), etc. Examples of conductive polymers may include polyaniline, polythiophene, polyacetylene, polypyrrole, etc. In some aspects, a mixture of conductive additives and / or binder materials can be used.
[0140] In various aspects, the positive electrode may include greater than or equal to 0 wt % to less than or equal to about 30 wt %, and in some aspects, optionally greater than or equal to about 2 wt % to less than or equal to about 10 wt % of one or more conductive additives; and greater than or equal to 0 wt % to less than or equal to about 20 wt %, and in some aspects, optionally greater than or equal to about 1 wt % to less than or equal to about 10 wt % of one or more binders. The positive electrode may include greater than or equal to 0 wt % to less than or equal to 30 wt %, and in some aspects, optionally greater than or equal to 2 wt % to less than or equal to 10 wt % of one or more conductive additives; and greater than or equal to 0 wt % to less than or equal to 20 wt %, and in some aspects, optionally greater than or equal to 1 wt % to less than or equal to 10 wt % of one or more binders.
[0141] In various aspects, the negative electrode can be prepared using a wet coating process without the need for an ionic liquid. However, in other variations, the negative electrode can also be prepared using a solvent-free process.
[0142] Certain features of the prior art are further illustrated in the following non-limiting examples. Example
[0143] Figure 6 is a scanning electron microscope (SEM) image of a comparative example, showing an anode comprising graphite 2000 and an electrolyte 1001 comprising Li6PS5Cl (LPSCl) solid electrolyte particles. Figure 7 is an SEM image of an embodiment, showing an anode 2000 comprising graphite and an electrolyte, wherein the electrolyte includes a first layer 100 adjacent to the anode 2000 comprising graphite and a second layer 200 opposite to the anode comprising graphite, wherein the first layer 100 includes LPSCl solid electrolyte particles and fibrils comprising carbon, fluorine and lithium and has a thickness of 10 micrometers (μrn), and the second layer 200 includes LPSCl solid electrolyte particles. Figure 7 The inset shows the delamination of the layers to more accurately measure the thickness of the first layer. The fibrils containing carbon, fluorine and lithium can be confirmed by energy dispersive X-ray spectroscopy mapping.
[0144] Figure 87 is a graphical representation of an x-ray photoelectron spectroscopy (XPS) analysis of a first layer of an embodiment, wherein the x-axis represents binding energy (electron volts (eV)), the y-axis 702 represents intensity (au), and curve 801 is the original, curve 802 is the fitted, and curve 803 is the baseline. As shown, the C1s and F1s XPS graphs show the presence of residual CF bonds, indicating that the lithium is completely consumed. If there is a residual lithium source, it will continue to react with the CF bonds to form LiF.
[0145] Fig. 9 is a graph showing the electrochemical performance of the comparative example, wherein the x-axis represents the specific capacity (mA-hour / gram (mAhg -1 )), the y-axis represents voltage (volts (V)). Fig.10 is a graph showing the electrochemical performance of the examples, wherein the x-axis represents the specific capacity (mAh g -1 ), the y-axis represents voltage (V). Fig.11 is a graphical representation of the electrochemical performance of the comparative example (1101) and the example (1102), wherein the x-axis represents the cycle number and the y-axis represents the specific capacity (mAh g -1 ).like Figure 9-11 As shown in , the examples exhibit improved capacity retention compared to the comparative examples. Without wishing to be bound by any theory, it is believed that better cycling performance can be achieved through the protection provided by the fibrils comprising carbon, fluorine and lithium.
[0146] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. The term "or" means "and / or" unless the context clearly indicates otherwise. Reference to "aspects" throughout the specification means that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various aspects.
[0147] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0148] Unless specified to the contrary herein, all test standards are the most recent standards in effect as of the filing date of the present application or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0149] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0150] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope thereof. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the substantive scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. An electrolyte for an electrochemical cell, the electrolyte comprising: a first layer having a thickness of about 1 μm to about 40 μm; and a second layer having a thickness of about 5 μm to about 60 μm, Wherein, based on the total weight of the first layer, the first layer comprises: about 10 wt % to about 40 wt % of first solid electrolyte particles, about 1 wt % to about 15 wt % lithium, and about 1 wt % to about 65 wt % of fibrils comprising carbon and fluorine, and The second layer comprises second solid electrolyte particles.
2. The electrolyte of claim 1, wherein the first layer further comprises greater than 0 to about 60 weight percent of a conductive material.
3. The electrolyte of claim 1, wherein the fibrils comprising carbon and fluorine comprise polytetrafluoroethylene.
4. The electrolyte of claim 3, wherein the fibrils comprising polytetrafluoroethylene are present in an amount of about 1 wt% to about 50 wt% based on the total weight of the first layer.
5. The electrolyte of claim 1, wherein the fibrils comprising carbon and fluorine further comprise lithium.
6. An electrochemical cell for cycling lithium ions, the electrochemical cell comprising: An electrolyte comprising: a first layer having a thickness of about 1 μm to about 40 μm; and a second layer having a thickness of about 5 μm to about 60 μm, Wherein, based on the total weight of the first layer, the first layer comprises: about 10 wt % to about 40 wt % of first solid electrolyte particles; about 1 wt % to about 15 wt % lithium; From about 1% to about 65% by weight of fibrils comprising carbon and fluorine; and greater than 0 to about 60 weight percent conductive material, and The second layer comprises second solid electrolyte particles.
7. The electrochemical cell of claim 6, wherein the fibrils comprising carbon and fluorine comprise polytetrafluoroethylene.
8. The electrochemical cell of claim 6, wherein the fibrils comprising carbon and fluorine further comprise lithium.
9. An electrolyte for an electrochemical cell, the electrolyte comprising: a first layer having a thickness of about 1 μm to about 40 μm; and a second layer having a thickness of about 5 μm to about 60 μm, Wherein, based on the total weight of the first layer, the first layer comprises: about 10 wt % to about 40 wt % of first solid electrolyte particles, wherein the first solid electrolyte particles comprise solid sulfide electrolyte particles; about 1 wt % to about 15 wt % lithium; From about 1% to about 65% by weight of fibrils comprising carbon and fluorine; and greater than 0 to about 60 weight percent conductive material, and The second layer comprises second solid electrolyte particles.
10. The electrolyte of claim 9, wherein the fibrils comprising carbon and fluorine are prepared from a starting polytetrafluoroethylene material having an average particle size of greater than or equal to about 2 μm to less than or equal to about 2,000 μm.